Clinical Management of Excessive Gingival Display with Lip Repositioning Surgery: A Case Report - Satrio, Loren Pandu; Carolina, Dyah Nindita; Bawono, Chandra Andi (Dentistry Faculty, 2025)
exposure of more than 2 mm of gingival tissue during smiling, often leading to aesthetic concerns, particularly in female patients. The etiology of EGD can be multifactorial, involving dentoalveolar causessuch as gingival overgrowth, altered passive eruption, and short clinical crownsor non-dentoalveolar causes such as vertical maxillary excess and hyperactive upper lip. Lip repositioning surgery (LRS) offers a conservative and minimally invasive alternative to orthognathic surgery in appropriate cases. Case Report: This case involves a 36-year-old female presenting with symmetrical facial proportions, competent lips, and excessive gingival display above the esthetic norm. Upon clinical evaluation, the primary contributing factor was identified as a hyperactive upper lip. The patient underwent lip repositioning surgery, which included partial-thickness incisions and mucosal strip excision in the maxillary vestibule to reduce lip elevation during smiling. The procedure was completed under local anesthesia with no intraoperative complications. At follow-up, the patient demonstrated significant improvement in smile aesthetics, with a notable reduction in gingival exposure and high levels of satisfaction. No adverse postoperative effects were observed. Conclusion: Lip repositioning surgery is a simple, safe, and effective technique for managing EGD caused by a hyperactive upper lip. It provides predictable aesthetic outcomes with minimal morbidity and is best indicated in cases with mild to moderate gingival display. Although short-term results are promising, long-term studies are needed to evaluate the stability and efficacy of the procedure over time.